MEMBANGUN BUDAYA ORGANISASI BERBASIS RELIGIUS - Husni, Muhammad; Puadi, Hairul (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2018)
Islamic as a religions of having standards and norms as a reference value follower. The values derived from thedoctrinesof religions was hitcertainly canbe applied live the lifeof the daily, includingin the organization. However islamicvalues inanything that canbe usedin buildingthe organization and how toimple mentthese values.Organizational cultureis builtwitha setthe with of valuet hatsurebyall behaviorinan organization ofit. Islamic as asou rceproc edureslso havethe valuest hatcanbe usedas building astrong the organizational of culture. The valuesin the organizationis also requiredto binding and ever yoneinthe organization to aunified whole.